2015
DOI: 10.3892/ijmm.2015.2438
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated growth factor increases Schwann cell proliferation and neurotrophic factor secretion and promotes functional nerve recovery in vivo

Abstract: Concentrated growth factor (CGF) is a newly generated complex that comprises a fibrin matrix incorporating growth factors and plasmatic and leukocyte cytokines. It has been widely used in bone regenerative medicine. However, the effect of CGF on peripheral nerve regeneration had not been previously investigated. The aim of the present study was to evaluate the possibility of using CGF for nerve regeneration by i) investigating the effect of CGF on the proliferation of Schwann cells (SCs) and secretion of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Most studies listed in Tables and have focused on proliferation and osteogenic differentiation. However, the effects of CGF on migration and endothelial differentiation or angiogenesis were also under investigation in four studies included in this review (Hong et al, ; Jin et al, ; Jun et al, ; Qin, Wang, Sun, et al, ). Improvement of cell migration is the result of a high concentration of chemotactic factors, such as PDGF‐BB and bFGF in CGF.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies listed in Tables and have focused on proliferation and osteogenic differentiation. However, the effects of CGF on migration and endothelial differentiation or angiogenesis were also under investigation in four studies included in this review (Hong et al, ; Jin et al, ; Jun et al, ; Qin, Wang, Sun, et al, ). Improvement of cell migration is the result of a high concentration of chemotactic factors, such as PDGF‐BB and bFGF in CGF.…”
Section: Discussionmentioning
confidence: 99%
“…18 By contrast, one study 82 reported that platelet gel with a collagen tube conduit did not have a beneficial effect on rat sciatic nerve regeneration 12 weeks after microsurgical reconstruction. However, 2 years later, the same group 83 observed that the same gel could have a positive effect on nerve repair.…”
Section: Prp Treatment: Preparation and Biological Characteristicsmentioning
confidence: 95%
“…17, 18 Thus, the following review summarizes the state-of-the-art application of PRP for recovery of injured peripheral nerves and offers an outlook on possible future use as an emerging strategy for osseoperception. The articles cited in the review, published up to the 15 November 2016 and including electronic early-release publications, were acquired using three databases: MEDLINE (PubMed), Web of Science (ISI Web of Knowledge) and OpenGrey (System for Information on Grey Literature in Europe).…”
Section: Introductionmentioning
confidence: 99%
“…As neuronal repair mechanisms might take a longer period of several months, previous work has proposed the delivery of growth factors in peripheral nerve repair (Qin et al, 2016). Numerous investigations have demonstrated that cavernous nerves can be successfully repaired using autologous nerve grafts and artificial conduits.…”
Section: Introductionmentioning
confidence: 99%